Development Strategy on Small Business with Business Model Canvas - Umar, Abdullah (International Journal of Technology And Business, 2018)
The price increase is happening at the moment, be it the price of basic necessities, electricity, water, and fuel is quite disturbing people. So that people should try different ways to make ends meet. Therefore, to cover all the necessities of life, so many people are trying to open a side business. Sideline is usually referred to by small businesses. Small businesses are often in the open, among others, selling pulses, food stalls, grocery store, laundry kilogram or photocopy services provider. But setting up a business is usually without a good strategy. This is due, many potential entrepreneurs have set up businesses just went along and imitate an existing business. So never think about how the business processes in accordance with his efforts. Therefore, this study is expected to be useful for prospective rulers to get an overview of the business to be run. So that it can determine what strategies will be used. Picture this business using the business model of the canvas, because in this business model can be known to target the business market, the value that can be provided to consumers, to anyone supplier or partner for the business. This study uses qualitative research methods include observation and interviews to several small businesses and uses business models study the literature on the canvas.